Review of Learning Management System in Current Scenario - Tripathi, Raghvendra Narain (Indian Journal of Computer Science, 2022)
A Learning Management System (LMS) is a software that is used to administer, automate and deliver courses. It is used for training and development of its members or employees by educational institutes, companies and government organizations. As the online education industry is growing rapidly, having a modern LMS becomes imperative to impart education and training on scale repeatedly. Audiences should be comfortable using LMS for it to be effective. This paper covers the uses, features, and architecture of an effective learning management system.